La formation des traditions de solidarité ouvrière chez les mouleurs Montréalais: la longue marche vers le syndicalisme (1859-1881) - Bischoff, Peter (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1988)
Abstract This paper examines the causes for the slow development of trade unionist traditions among Montreal moulders. Founded in 1859, the Montreal moulders' union underwent two decades of relative stagnation, before experiencing an important expansion. During the same period, in other Canadian towns, the moulders rapidly formed strong unions. In Montreal, ethnic and linguistic differences between the British and French Canadian moulders, and the tensions they engendered during the period, seem to have been at the center of the problem. Only a minority of moulders, primarily those of Scottish, Irish, English, and American origin, were involved in the union from the outset. The non-unionized moulders, mainly French Canadians, apparently opted for a more spontaneous form of militancy. Often organizing on a temporary basis, their position was solidified by their functional autonomy in the workplace. But in the long run, through a lengthy process of adaptation, and under the threat of degradation of their craft, the moulders closed ranks around a permanent organization of regulation and defense of their trade. The union's rise was carried out under the impulse of the French-Canadian moulders, and secondary, the Irish-Canadian moulders.